Determination of the Effect of Price Fluctuations on Producer Income – the Case of Potatoes - Hasan Arısoy; Zeki Bayramoğlu (Turkish Journal of Agriculture: Food Science and Technology)
Prices of agricultural products fluctuate depending upon several factors. In Turkey, potatoes are one of the main products for which price fluctuations are observed. This study was undertaken to determine the effect of the fluctuation in potato prices on producer incomes in Turkey. The Neyman Method was used to determine the sample size. The number of enterprises required to achieve a representative sample size was determined to be 56, with a 5% error margin and a 95% reliability limit. The way in which the potato cultivation area is affected by price was examined. The Koyck model was utilized for this purpose. By using Koyck analysis, average lag time was calculated to be approximately 1 year. This result indicates that the fluctuation in potato prices has quite a rapid effect on production. It was determined that producer income varies greatly depending on annual potato prices. The difference between estimated potato price and the actual price for the year 2012 resulted in an income loss of 11,198.6 $/ha. Some sustainable efforts such as production planning can be recommended to prevent these price fluctuations.